Energetic valorization of MSW compost valorization by selecting the maturity conditions. (15th May 2019) - Doña-Grimaldi, V.M.; Palma, A.; Ruiz-Montoya, M.; Morales, E.; Díaz, M.J.
Abstract: MSW compost valorization under combustion, at two different composting process conditions, have been studied by thermogravimetric analysis (TGA). The composting operating parameters such as aeration and moisture affect the biodegradability of compost and results of the combustion (different gross heating values for each reactors). The obtained TGA showed that maximum weight loss for 10–12% (245–247 °C), 32–34% (407–411 °C) and 44–46% (760–769 °C) in correspondence to hemicellulose, cellulose and lignin-humic-fulvic acids decomposition for each reactor are observed. Obtained valued in kinetic study (Flynn-Wall-Ozawa method) results in suitable coefficients of determination. In that form, to establish the assumption that combustion of compost under a first-order reaction may be appropriate. Moreover, in both reactors, the conversion rate increased and the activation energy decreased with composting time is found. The maximum gross heating value versus minimum activation energy (for α = 0.25 and α = 0.5) corresponds to final composts and under aeration of 0.050 and 0.175 Lair kg −1 d −1 and moisture of 40% and 55% for R1 and R2 reactors respectively. For MSW, under proper conditions, composting could be used as a suitable biodrying process, stabilizing and concentrating the heating value. Highlights: Thermal behaviour of MSW compost under combustion process. TGA results have been utilized to determine kinetic parameters by FWO method. Composting could be used as suitable process for concentrating the heating value.